The fleet that came to stay. - United States. Navy Department (Washington : The Dept., 1945)
Explains the invasion of Okinawa from the U.S. Navy point of view and illustrates the operation by scenes of the combat.
With: Fury in the Pacific -- Remember these faces.
Videocassette copy.
Order no. MN5802.
Keywords: World War, 1939-1945 -- Campaigns -- Japan -- Okinawa Island